NOT1CE - The Nocturnal Type 1 Caregiving Experience: A mixed-methods exploration of the nocturnal burden of care experienced by parent caregivers for juveniles with Type 1 Diabetes - Howard, Vivienne Ann (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2026)
Illness management in Type 1 Diabetes (T1D) is complex and onerous, requiring constant vigilance to manage insulin therapy and control blood glucose. For some parents of juveniles with T1D, care is a 24-hour responsibility. However, current care guidelines do not address nocturnal caregiving and little research attention has been paid to this topic to date. This PhD project was conceived to address this gap and highlight a relatively neglected issue in Type 1 Diabetes. This dissertation comprises five interrelated, mixed-methods observational studies, benefitting from collaboration with a public and patient (PPI) panel throughout. Study 1 involved a systematic literature review (SLR). Very high levels of nocturnal caregiving were found among T1D caregivers in the studies reviewed (88%), with 54% reporting substantial sleep disruption, resulting in fatigue, mood dysregulation, cognitive difficulties and impacts on physical health. 83% of authors recommended that sleep be routinely addressed in clinic, which is not current practice. Study 2 entailed the co-design of two novel caregiver self-report tools, in collaboration with the PPI panel, to facilitate an investigation into the Fear of Hypoglycaemia construct. In study 3, a mixed-methods online survey enquired into the value of the Fear of Hypoglycaemia construct from the perspective of parent caregivers (n=123), findings indicated that the construct sometimes mischaracterised attentive caregiving as maladaptive. Study 4 was a cross-sectional, mixed-methods survey designed to explore the SLR findings from study 1 within the Irish context (n=239). Here, 76% of caregivers reported sleep disruption and reduced sleep quality, with multiple impacts from fatigue detailed, among these, 37.5% reported negative impacts on their physical health. However, 73% had never discussed the nocturnal care burden in their clinics. The final study of this series, study 5, was a qualitative exploration of caregivers requirements for support (n=21). Participants indicated that sleep interference was considerable, but that hybrid closed-loop technology was helpful. Nonetheless, they would like this burden to be acknowledged and addressed during routine clinical contacts, and they would welcome 24-hour phone access to a diabetes nurse specialist. Collectively, these findings provide compelling evidence for the significance of the under-recognised issues associated with nocturnal caregiving in T1D and makes actionable recommendations for addressing it.
APPROVED
Keywords: Parent caregivers; Nocturnal caregiving; Care burden; Diabetes management; Sleep disruption; Participatory research; Paediatric Type 1 Diabetes; Systematic literature review; Public and patient involvement (PPI); Fear of Hypoglycaemia